Multi-floor map matching in indoor environments for mobile platforms - Ascher, C.; Kessler, C.; Weis, R.; Trommer, G. F. (2012 International Conference on Indoor Positioning and Indoor Navigation, 2012)
In this paper a map matching algorithm for multi floor indoor environments including guidance of a user is presented. Inertial sensor based pedestrian navigation systems are subject to drift. Maps are to eliminate that drift by matching the path to a map. In multi floor scenarios, we propose to use not only flat floor plans but also transitions like staircases as well as ladders and elevators. This is essential for an enhanced matching of a user path to a given 3D floor plan. Especially in industrial applications this is a crucial factor as also ladders and elevators exist. In contrast to other authors, this paper considers all of these objects. 3D position estimations from an Integrated Pedestrian Navigation System (IPNS) including an inertial system as well as a barometer and a magnetometer are used. Maps must be available, either from a prior Simultaneous Localization and Mapping (SLAM) survey or from facility maps. The new map representation is used to match real sensor data from the IPNS system to a map in a real time implementation. Furthermore an online guidance implementation is presented which is also based on the new 3D map representation.